2017
DOI: 10.1073/pnas.1621363114
|View full text |Cite
|
Sign up to set email alerts
|

cGAS is essential for the antitumor effect of immune checkpoint blockade

Abstract: cGMP-AMP (cGAMP) synthase (cGAS) is a cytosolic DNA sensor that activates innate immune responses. cGAS catalyzes the synthesis of cGAMP, which functions as a second messenger that binds and activates the adaptor protein STING to induce type I interferons (IFNs) and other immune modulatory molecules. Here we show that cGAS is indispensable for the antitumor effect of immune checkpoint blockade in mice. Wild-type, but not cGAS-deficient, mice exhibited slower growth of B16 melanomas in response to a PD-L1 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
357
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 453 publications
(394 citation statements)
references
References 31 publications
12
357
3
5
Order By: Relevance
“…However, it will be very interesting to test whether cGAS deletion promotes tumor development driven by oncogenes such as Ras, which is known to induce senescence. In this context, we recently reported that cGas-deficient mice are refractory to the antitumor effect of immune checkpoint blockade in a syngeneic tumor transplant model (42), indicating that cGAS is required for generating intrinsic antitumor immunity. It remains to be determined whether cGAS has a cellautonomous function in impeding the transformation of a normal cell into a cancer cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it will be very interesting to test whether cGAS deletion promotes tumor development driven by oncogenes such as Ras, which is known to induce senescence. In this context, we recently reported that cGas-deficient mice are refractory to the antitumor effect of immune checkpoint blockade in a syngeneic tumor transplant model (42), indicating that cGAS is required for generating intrinsic antitumor immunity. It remains to be determined whether cGAS has a cellautonomous function in impeding the transformation of a normal cell into a cancer cell.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that senescence may act as a barrier to tumor progression. Our findings that cGAS is required for senescence and our previous findings that cGAS is important for antitumor immunity predict that cGAS may be a tumor suppressor under some circumstances (42). To test this possibility, we carried out bioinformatics analyses of publicly available gene expression datasets, including The (human) Cancer Genome Atlas (TCGA), the Gene Expression Omnibus (GEO), and the Cancer Biomedical Informatics Grid (caBIG).…”
Section: Low Expression Of Cgas Is Correlated With Poor Survival Outcmentioning
confidence: 99%
“…Moreover, many patients suffer severe adverse effects, especially when treatments are combined (37). Recently, endogenous IFN was shown to be involved in immune checkpoint blockade efficacy (11)(12)(13)38). Anti-PDL1 sdAb therapy added to the tumor stasis effect of Clec9A-mAFN in the B16 tumor model (Fig.…”
Section: Complete and Safe Tumor Eradication By Dc-targeted Afn In Comentioning
confidence: 99%
“…Several host immune cells, including dendritic cells (DC), T and B lymphocytes, natural killer (NK) cells, and macrophages, all respond to IFN and may be involved in antitumor activity (2,5). Furthermore, endogenous IFN is essential for cancer immunosurveillance (6,7), and for anticancer therapies including chemotherapy, radiotherapy, immunotherapies, and checkpoint inhibition (5,(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Mice deficient in IFN-I signaling display enhanced susceptibility to tumor formation [38 • ], and IFN-I signaling is critical for the development of anti-tumor activity of NK cells [39 • ] as well as antigen cross-priming of tumor-specific CD8+ T cells by DC [40 • ,41 • ]. Among an array innate immune signaling molecules examined for an essential role in tumor growth and immunogenicity, STING and cGAS appear to be uniquely indispensable for natural or spontaneous anti-tumor immunity [42 •• ,43 •• ], as well as the immunogenic effects of irradiation [44 •• ], CD47 blockade [45], and immune checkpoint therapy [46]. Accordingly, cGAMP is a potent anti-tumor agent against many solid and suspension tumor types [4750].…”
Section: Cancer Cancer Therapy and Genotoxic Stressmentioning
confidence: 99%